Analysis of Daily Rainfall Extremes in Iraq - Al-Budeiri, Ahmed (Al-Adab Journal, 2024)
Understanding the spatial and temporal patterns of the rainfall extremes and their variations is fundamental to reduce the impact of risks associated with those phenomena in light of global warming. Accordingly, the current study, significantly, provides an estimation to the temporal and spatial trends of rainfall extreme indices in Iraq over the period (1985-2020). Relied on the data of the Iraqi Meteorological Organizations for ten climate stations, eight indices to determine rainfall extremes are assessed. The linear test equation test has been used. The results showed the presence of varying trends in most rain extreme indicators: the annual rainfall amount index for wet days (PRCPTOT) recorded an increasing trend, amounting to (2.8 mm) with a decrease in some areas. The daily rainfall intensity index (SDII) also increased by (0.19) mm with a decrease in some northern and western regions. The two indicators (R10, R20) verified a slight increase with a decrease in some southern, northern and western regions. The two indicators (R95, R99) acknowledged a noticeable increase by (2.5, 2.7) mm per decade, respectively, in Iraq, with an obvious decrease in the Basra station by (-6.9 - -4.9) mm, respectively. As for the successive drought days index (CDD) indicated a clear decrease amounting to (-4.9) mm per decade, with an increase in some stations (RUTBA, BAIJI, KIRKUK), the indicator of the number of successive wet days (CWD) showed a slight increase (day per decade). The current study comes up with that the phenomenon of Climate change and its fluctuations plays a vital role in increasing the cases of changes in rainfall extremes indicators, which can be regarded as great challenge and danger to future generations. Additionally, the results of the study can help in assessing the risks of rainfall phenomena such as drought and floods.